(untitled) (Plant Tissue Culture and Biotechnology, 2026)
Anther culture-based doubled haploid (DH) technology offers an efficient approach for accelerating homozygosity in eggplant, although its application is often limited by strong genotype dependency and inconsistent regeneration. In this study, a set of F1 hybrids developed through a half-diallel mating design using drought-tolerant and high-yielding parental lines were evaluated for androgenic responsiveness under controlled in vitro conditions. Significant variation was observed among crosses for embryo-like structure (ELS) induction, green plantlet regeneration, and the composite Androgenic Index (AI). The diallel matrix revealed that several combinations, particularly RWE P11-2 × BP20-3, BP20-3 × RWE ©, B. Baria × BP20-3, and 3 (8) × BP20-3, showed superior ELS formation and regeneration efficiency, while albino production remained minimal across the population. Ranked AI values and Tukey groupings further identified RWE P11-2 × BP20-3 as the most promising cross for DH production. The results demonstrate strong parental effects on androgenesis, with BP20-3 and RWE P11-2 functioning as consistently responsive parents. Overall, this study highlights the potential of drought-adapted eggplant germplasm for efficient DH line development and provides valuable insights for integrating half-diallel-based selection with haploid breeding strategies. Plant Tissue Cult. & Biotech. 35(2): 381-388, 2025 (December)